The Current Status of Ultrasound Education in United States Medical Schools. (15th January 2021) - Nicholas, Elizabeth; Ly, Alan A.; Prince, Anna M.; Klawitter, Paul F.; Gaskin, Kevin; Prince, Louise A.
Abstract : Objectives: Ultrasound is used by nearly every medical specialty. Medical schools are integrating ultrasound education into their curriculum but studies show this to be inconsistent. The purpose of this study was to provide an updated description of ultrasound in the curricula of United States Accredited Medical Schools (USAMS). Methods: In 2019, USAMS curricular offices were contacted. Institutions were asked about the presence of ultrasound curriculum and for contact information for faculty involved with education. Schools reporting ultrasound curriculum were surveyed regarding details of their curriculum. Results: Two hundred USAMS were contacted with a response rate of 84%. Of 168 schools, 72.6% indicated they have an ultrasound curriculum. For schools with a curriculum, 79 (64.8%) completed our survey. The majority of survey respondents, 66 (83.5%), indicated having mandatory ultrasound. Ultrasound is primarily integrated into courses (73.8% in basic science courses, 66.2% in clinical skills courses, and 35.4% in clinical rotations). Emergency medicine physicians accounted for 54.7% of course directors. Ten or fewer faculty participate in education in 68.4% of schools and mostly as volunteers. Dedicated machines for education were reported by 78.5% of schools. Conclusions: Compared to prior studies, this study had a higher response rate at 84%, and more schools reported ultrasound in their curricula. Emergency medicine represents the majority of leadership in ultrasound education. Despite increased integration of ultrasound into American medical school curricula, its instruction is still inconsistent.